A Crown For Lion - A.H. Benjamin (Bharat Franklin Watts, 2017)
In this fun, animal story, Lion is looking for a crown - he wants everyone to know he is the king. The animals try many different things, but nothing seems to work... until Lion has a sneezing fit!
Keywords: Independent Reading -- Independent Reading